Ecologia da comunidade de aranhas de solo de uma área de cerrado no sudeste do Brasil - Mineo, Marina Farcic (2009)
Despite being extremely abundant and diverse, ground-dwelling spiders are poorly known in Brazil. The present study, conducted between April 2005 and February 2007, investigates the composition, richness and diversity of ground-dwelling spiders, as well as the influence of seasonality on them and the structure of this community. It was carried out at the Panga Ecological Station in the State of Minas Gerais, southeastern Brazil. Three very distinct phytophysiognomies (campo cerrado, cerrado and cerradão) were sampled using pitfall traps during five days every two months. A total of 3,477 spiders of 112 species and 31 families were found. At least eight new species were found and one species, Trocantheria gomezi (Trochanteridae), was recorded for the first time in Brazil. All sites presented unique species compositions, richness and diversity. Increased abundance and richness were observed during the wet season. The peak of individuals was in October and April registered the lowest abundance. Furthermore, the first ecological data for Tenedos perfidus (Zodariidae), an endemic species of this Ecoregion, was presented. Between the eight guilds found, active hunters on the ground were the most abundant in the three habitat types, followed by web-builders and ambushers. The community structure vary between phytophysiognomies and between seasons. Abundance per guild was higher during wet season. The diversity among ground-dwelling spiders in Brazilian Savannas is very heterogeneous and pointed out the importance of conserving different habitat types for the maintenance of their biodiversity.